The Use of the Miro Digital Tool in Managing Learning to Promote Teamwork Competencies Among Students in the Elementary Education Program at Valaya Alongkorn Rajabhat University under the Royal Patronage - Thanachaiworaphan, Waranit (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This study aims to enhance the necessary competencies that students can apply to develop future learners at the elementary education level. This research aimed to investigate the impact of using the digital tool Miro in learning management to promote teamwork competencies among elementary education students. Methodology: The target group for this study consisted of 22 second-year students majoring in elementary education at Valaya Alongkorn Rajabhat University Under the Royal Patronage during the academic year 2566. The research instruments were four activity plans with the digital tool Miro and a teamwork competency assessment, which was administered before, during, and after the experiment. Data analysis involved comparing average scores before, during, and after the experiment. Statistical analysis involved mean, standard deviation, and repeated measures ANOVA. Results: The findings revealed statistically significant differences at .05 level in teamwork competency scores at various points in time. The average teamwork competency scores increased after the experiment compared to before and during the experiment. The research suggests that using Miro as a digital tool for collaborative learning positively impacts teamwork competencies among elementary education students. Conclusion: The average teamwork competence scores, measured at different time intervals, show a statistically significant increase after the experiment compared to before. The study suggests that the use of the digital tool Miro in learning management effectively promotes enhanced teamwork competence among elementary education students.